ANALISIS PEMBELIAN ULANG SUBWAY DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Rahmad Rivaldi (2023)
This study analyzes subway repurchases with customer satisfaction as the intervening variable. The purpose of this research is to examine the factors that can affect customer satisfaction. The factors studied are product quality, service quality, and price. This research is quantitative by distributing questionnaires to 130 respondents who have purchased subway products in the South Jakarta area. This study uses the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) alternative with the Smart-PLS program. The results of the data analysis show that: (1) product quality has an effect on customer satisfaction (2) service quality has no effect on customer satisfaction (3) price has an effect on customer satisfaction (4) customer satisfaction has an effect on repeat purchases (5) product quality and price have an effect on repurchase through customer satisfaction but do not mediate the relationship between service quality on repurchase.